2000
DOI: 10.1046/j.1365-3083.2000.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

CD135 (Flk2/Flt3) Expression by Human Thymocytes Delineates a Possible Role of FLT3‐Ligand in T‐Cell Precursor Proliferation and Differentiation

Abstract: The expression of the Flk2/Flt3 molecule (CD135), the receptor for Flt3 ligand (FL), was investigated in the human thymus. Results showed that there is a high level of expression of CD135 by thymocyte populations, especially by intrathymic T-cell precursor populations. As these results suggested a role for FL in the regulation of thymic T-cell precursor differentiation and/or proliferation, we used an in vitro model of thymic stromal cell cultures in order to delineate the activity of FL on human CD7(high)CD3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…25 This may resemble aspects of FLT3 mutation in human AML. 17 In murine thymocytes, Flt3 signaling may induce myeloid differentiation, 36 consistent with changes in Hox expression. Mizuki et al 37 reported that FLT3 activation is associated with downregulation of Pu.1 and CEBPa in 32Dcl3 cells.…”
Section: Discussionmentioning
confidence: 84%
“…25 This may resemble aspects of FLT3 mutation in human AML. 17 In murine thymocytes, Flt3 signaling may induce myeloid differentiation, 36 consistent with changes in Hox expression. Mizuki et al 37 reported that FLT3 activation is associated with downregulation of Pu.1 and CEBPa in 32Dcl3 cells.…”
Section: Discussionmentioning
confidence: 84%
“…19 This case had strong myeloid gene expression, similar to the MLL B-ALL cases, except that high levels of granulocytic genes predominated in the FLT3-ITD T-ALL case, while monocytic genes predominated in MLL B-ALLs ( Figure S3, supplemental material). Finally, FLT3 activation has been shown to induce myeloid differentiation of T-cell precursors 47 and may contribute to the myeloid features of MLL B-ALLs as well. 12 In any case, it is unlikely that myeloid genes are related to the oncogenic transcriptional program associated with MLL (ie, up-regulation of selected major HOX genes together with MEIS1) as they are found only in MLL B-ALLs but not in MLL T-ALLs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] During normal lymphopoiesis, CD117/KIT is expressed by a fraction of CD34 ϩ CD3 Ϫ CD4 Ϫ CD8 Ϫ (triple-negative) thymocytes, which have not yet rearranged their T-cell receptor (TCR) genes. 4 In these thymocytes, 5 as in normal bone marrow progenitors, 6 expression of CD117/KIT coincides with that of CD135, the FLT3 receptor tyrosine kinase (RTK) that is activated by the FLT3 ligand. FLT3 and CD117/KIT share extensive structural homology.…”
Section: Introductionmentioning
confidence: 96%
“…7 Treatment with FLT3 ligand and stem cell factor elicits in vitro differentiation of CD117/KIT ϩ CD135/ FLT3 ϩ T-cell progenitors toward the myeloid lineage, whereas stem cell factor together with interleukin-7 induces development toward a mature T-cell phenotype. 5 Activating mutations of FLT3 are the most common genetic abnormality found in acute myeloid leukemia (AML) and encode a protein with constitutive RTK activity in the absence of ligand. 6 While the majority of FLT3 mutations are internal tandem duplications (ITDs) located in the juxtamembrane domain of the receptor, some leukemias instead harbor point mutations in the activation loop of the kinase domain.…”
mentioning
confidence: 99%